Village-Owned Enterprises Development: HR Innovation Barriers in Ketapang Village, Sidoarjo: Perkembangan Usaha Milik Desa: Hambatan Inovasi Sumber Daya Manusia di Desa Ketapang, Sidoarjo - Nasrul , Amak; Choiyirah, Ilmi Usrotin (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Sustainable rural development hinges on empowering local economies, with Village-Owned Enterprises (BUMDes) serving as the primary vehicle for achieving community welfare. Specific Background: The Village Government plays a crucial statutory role as regulator, dynamizer, facilitator, and catalyst to ensure BUMDes' success, as mandated by the Village Law in Indonesia. Knowledge Gap: While the government's role is well-defined, the specific challenges encountered in operationalizing this role and their direct link to the BUMDes' success in a particular region require detailed examination. Aims: This research analyzes and describes the Village Government's multifaceted role in developing BUMDes in Ketapang Village, Sidoarjo. Results: The government actively provides capital (e.g., Rp 230 million for Califour Tourism) and technical training, but the primary constraint is the BUMDes management's lack of innovation, digital promotion skills, and general capability. Novelty: This study provides empirical evidence of how the government's four roles (Regulator, Dinamizator, Facilitator, Catalyst) interact with specific HR and financial limitations in Ketapang Village, offering precise local solutions. Implications: To achieve sustainable development, the government must shift its focus from general training to targeted capacity-building programs that specifically address human resource quality and digital literacy. Highlights: Village Government actively provides capital and regulatory support to BUMDes units. Development is primarily hindered by low human resources capability and innovation. Training efforts must be re-focused on BUMDes managers' digital and managerial skills. Keywords: Village Government, BUMDes, Local Economy, HR Obstacles, Rural Development